(untitled) (Książnica Śląska, 2025)
The subject of the text is a publication by J. Juraszek entitled “Składnia słowa łacińskiego w formie słownika” [Syntax of the Latin word in the form of a dictionary], which was published in Katowice in 1927. The article contains its description and analysis from the point of view of metalexicographical knowledge. Among the major issues discussed are: the genological status of the work, the problem of its authorship, the relations to other pedagogical and lexicographical works and the author’s workshop. The observations reported on the technical and linguistic layer of the publication allow us to propose the hypothesis that it was the result of a small-scale project, initiated by a private author (teacher), who was deeply inexperienced in the art of dictionaries. However, the unprofessional nature and lack of advanced proofreading or further editorial care do not change the fact that “Syntax of the Latin Word…” is the only Latin dictionary published in Katowice and Upper Silesia.